(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
The ternary systems of Co(II), Ni(II), and Cu(II) complexes containing L-Histidine as primary ligand and 1,10-Phenanthroline as secondary ligand are studied in aqueous medium mixed with different amounts of 1-propanol. Through pH metric technique the stability constants were obtained for the complexes formed at 303K and ionic strength of 0.16 mol/L maintained with NaCl. The predominant species detected are MLXH and ML2X which were refined by using the computer program MINIQUAD75. The best-fit chemical models were selected Based on statistical parameters. The relative stabilities of the ternary complexes as well as the distributions of all the complexes in solution were explained.